Research exploring greenhouse environment control over the last 50 years - Takakura, Tadashi (International Journal of Agricultural and Biological Engineering, 2019)
Environments do not exist in isolation. Their main components in greenhouse systems are plants. Without consideration of plants, analysis of greenhouse environments and environmental control of greenhouses can be accomplished, although it is not simple to achieve. Initial attempts were undertaken to analyze greenhouse environments and then reproduce them. Ventilation rate effects on plant photosynthesis in a growth chamber were reported in 1966. Computer simulations then became a main subject of research. The first dynamic computer simulation of a greenhouse environment including plants was published in 1971. According to innovations of computer technology, the use of minicomputers and microcomputers spread in many areas. By measuring the net photosynthesis of lettuce plants grown under artificial lighting, air temperature was optimized using a minicomputer with the hill-climbing method. The method was designated as the Speaking Plant Approach to environment control (SPA). After the author developed the first reported environmental control system in Japan, systems using microcomputers spread widely for greenhouse environmental control. Knowledge-based expert systems were tested for plant management. Also, a machine vision system was developed to detect critical moments for watering of muskmelon plants. The first feed-forward control method for greenhouses with a large heat mass was reported. Then space farming was tested in 1996 to assess gravity effects on plants. Energy-saving aspects such as solar sterilization, ground heat storage system, and storage using phase change material (PCM) have been reported. Defects of ordinary solarimeters were reported in 2008 along with an approach to estimate evapotranspiration in a greenhouse without the effect of so-called cosine law. Later, this technique was expanded to estimate photosynthesis of the plant canopy in a greenhouse using newly developed sensor units. Keywords: computer control, evapotranspiration, global and diffused solar radiation, nondestructive and non-contact measurement, photosynthesis, SPA DOI: 10.25165/j.ijabe.20191205.5179 Citation: Takakura T. Research exploring greenhouse environment control over the last 50 years. Int J Agric & Biol Eng, 2019; 12(5): 1–7.